Prediksi Kebutuhan Air PDAM Kota Malang Menggunakan Metode Fuzzy Time Series Dengan Algoritma Genetika - Khaira Istiqara; Muhammad Tanzil Furqon; Indriati Indriati (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Water is one of the basic needs of living things derived from natural resources. The Government provides a regional water company called Perusahaan Daerah Air Minum (PDAM) to fullfil the clean water needs of the people of Indonesia, one of which is located in Malang. PDAM water needs prediction system serves to predict the water needs of the people of Malang, so water needs will be guaranteed in the future. Variable used is PDAM water usage data from 2008-2013. Genetic algorithms are used to optimize the subset of universe in fuzzy time series. Search solution uses real-coded chromosome representation, then processed with genetic operator (crossover, mutation and selection). Method of genetic operator used is one-cut-point crossover, uniform mutation and elitism selection. The result of testing genetic algorithm parameter values, obtained the optimal population size is 360, the length of chromosome is 60, the best combination of crossover rate and mutation rate are 0.4 and 0.2, and the number of optimal generation is 550. Based on the best genetic algorithm parameter value, obtained the prediction result with the error value (MAPE) is 2.266776%. These results showed a good predictive ability with low error values.